The Determinants of Capital Structure: An Empirical Investigation of Malaysian Listed Government Linked Companies - Ab Wahab, Siti Nur Aqilah; Ramli, Nur Ainna (International Journal of Economics and Financial Issues, 2014)
In this study, we explore how the debt equity choices of Listed Malaysian Government linked Companies (GLCs) are influenced by the firm specific characteristics and macroeconomic variables using a sample of 13 GLCs from 1997 to 2009. Two elements of leverage, book value of total debt ratio (BVTDR) and long term debt ratio (BVLTDR), were used to check for any significant changes in corporate financing and found mixed results. Tangibility and firm size are the most significant variables to determine the corporate financing of GLCs. Liquidity and interest rate are negatively significant with BVTDR and BVLTDR, respectively.The study concluded that profitability is inconsequential in determining corporate financing; inconsistent with the findings of previous Malaysian studies. With the proper design of capital structure and intervention from the government, the study also concludes that GLCs are rely less on leverage to support their investment activities. Keywords: Capital structure; Pecking Order Theory; Trade-Off Theory JEL Classifications: G32; F62